Reorganisasi Struktur Pemerintahan Di Daerah Pemekaran Studi kasus Kabupaten Solok Selatan Propinsi Sumatera Barat - A, Efrianto. (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2011)
Reformation has rised the spirit of outonomy in local area. TheLocal Outonomy rules with Law of 22th 1999 year, Law of 25th 1999year and also the 129th year 2000 of Goverment Regulation. ThatRegulation has caused the change on Indonesia government system. Since2007, there have been performed 167 regions and provinces. ThisCondition has been bringing to local society impacts because formedthe new areas continued with forming lower local areas, till lowerst areasof goverment. This research descrips the change on South Solok Regionafter it have been formed and opened in 2003 year.Keywords : local outonomy, local government, regions forming